1, 10-Phenanthroline decorated with substituent groups forming europium(III) complexes: synthesis, crystal structure, photoluminescence properties and their bioimaging in living cells. Issue 16 (17th August 2020) - Song, Huimin; Fan, Congbin; Wang, Renjie; Wang, Zheng; Pu, Shouzhi
Abstract: With 2-thenoyltrifluoroacetone (tta) as the first ligand and phenanthroline derivatives as the second ligand, two europium(III) complexes, Eu(tta)3 L1 (L1 = 11-nitrodipyrido[3, 2-a:2', 3'-c]phenazine) (1 ) and Eu(tta)3 L2 (L2 = 11-methoxydipyrido[3, 2-a:2', 3'-c]phenazine) (2 ), have been synthesized and their structures were characterized by NMR and single-crystal X-ray crystallography. The two complexes exhibited red emissions that belonged to 5 D0 → 7 Fj (j = 0-4) transitions of Eu in different solutions and solid state. Complex 2 with the electron-donating group showed preferable luminous properties to that of complex 1 with the electron-withdrawing group. Moreover, complex 2 displayed much longer lifetimes, higher quantum yields and better CIE color coordinates corresponding to pure red in color ( x  = 0.67, y  = 0.33). In addition, the two complexes had strong intracellular luminescence, which indicated that they could be employed in luminescence imaging of living cells. GRAPHICAL ABSTRACT: